Mitochondrial Cumulative Damage Induced by Mitoxantrone: Late Onset Cardiac Energetic Impairment - Rossato, Luciana Grazziotin (2014)
Mitoxantrone (MTX) is a chemotherapeutic agent, which presents late irreversible cardiotoxicity. This work aims to highlight the mechanisms involved in the MTX-induced cardiotoxicity, namely the effects toward mitochondria using in vivo and in vitro studies. Male Wistar rats were treated with 3 cycles of 2.5 mg/kg MTX at day 0, 10, and 20. One treated group was euthanized on day 22 (MTX22) to evaluate the early MTX cardiac toxic effects, while the other was euthanized on day 48 (MTX48), to allow the evaluation of MTX late cardiac effects. Cardiac mitochondria isolated from 4 adult untreated rats were also used to evaluate in vitro the MTX (10 nM, 100 nM, and 1 lM) direct effects upon mitochondria functionality. Two rats of MTX48 died on day 35, and MTX treatment caused a reduction in relative body weight gain in both treated groups with no significant changes in water and food intake. Decreased levels of plasma total creatine kinase and CK-MB were detected in the MTX22 group, and increased plasma levels of lactate were seen in MTX48. Increased cardiac relative mass and microscopic changes were evident in both treated groups. Considering mitochondrial effects, for the first time, it was evidenced that MTX induced an increase in the complex IV and complex V activities in MTX22 group, while a decrease in the complex V activity was accompanied by the reduction in ATP content in the MTX48 rats. No alterations in mitochondria transmembrane potential were found in isolated mitochondria from MTX48 rats or in isolated mitochondria directly incubated with MTX. This study highlights the relevance of the cumulative MTX-induced in vivo mitochondriopathy to the MTX cardiotoxicity.